Elasticity of neck muscles in cervicogenic headache - Sedlackova, Zuzana; Vita, Martin; Herman, Jan; Furst, Tomas; Dornak, Tomas; Herman, Miroslav (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2022)
AIM: To compare the elasticity of the sternocleidomastoid and trapezius muscles in patients with cervicogenic headache and in healthy volunteers. METHODS: The medical history of 23 patients with cervicogenic headache was taken with a focus on pain characteristics. Elasticity of the sternocleidomastoid and trapezius muscles was measured by using shear wave elastography. Results were then compared with 23 healthy volunteers. RESULTS: The sternocleidomastoid muscle was significantly stiffer in patients with cervicogenic headache compared to healthy volunteers. The stiffness increased gradually from the parasternal area, where it was negligible, to the area near the mastoid process where it reached over 20 kPa. There was no difference in the stiffness of the trapezius muscle. The stiffness of the sternocleidomastoid muscle does show a significant dependence on headache characteristics (e.g., laterality, severity, or frequency). CONCLUSION: The results of this pilot study show that patients with cervicogenic headache have a higher stiffness of the sternocleidomastoid muscle than healthy volunteers. These findings suggest that elastography could be used as a diagnostic tool in cervicogenic headache.
Keywords: pilotní projekty; posttraumatická bolest hlavy; Pilot Projects; shear wave elastography; elastografie; Elasticity Imaging Techniques; pružnost; Post-Traumatic Headache; Humans; trapezius muscle; lidé; cervicogenic headache; sternocleidomastoid muscle; krční svaly; Neck Muscles; Elasticity